Supporting Primary School Children's learning in Digital Spaces at Home: Migrant Parents' Perspectives and Practices. (9th June 2019) - Tour, Ekaterina
Abstract : Using a sociocultural perspective and a case study design, this research examined how three migrant parents in Australia viewed and supported children's learning in digital spaces and the reasons behind these perspectives and practices. The study found that the participating parents mainly valued and actively supported technology‐based mechanical learning of print‐based literacy and numeracy basics and disregarded the development of digital literacies. The participants' views and practices were shaped by their desire for children's social mobility, driven by their migration status and high educational levels, and further reinforced by their interpretations of what was valued in the Australian education system.